Effects of surface modification on the properties of pineapple leaf fiber (PALF) reinforced with poly(lactic acid) (PLA) biocomposite / Shamimi Iwana Mohd Ismail - Mohd Ismail, Shamimi Iwana (2024)
Pineapple leaf fibre (PALF) is a natural fibre with significant promise in the industry. Reinforced polymer composites are now primarily relying on natural fibres as an alternative source. The aim of this study is to examine how the mechanical properties of PLA biocomposites reinforced with pineapple leaf fibre are affected by chemical treatments with Sodium Hydroxide (NaOH) solution. The biocomposite was successfully prepared by the solvent casting method. The characterization of biocomposite includes Fourier Transform Infrared Spectroscopy (FTIR) and tensile tests. The variation in loadings of pineapple leaf fibres (PALF) used in this study are 0%, 1%, 3%, 5% and 7%. The analysis of the study has shown that increasing the PALF loading decreases the tensile strength of the biocomposite. In the water immersion test, increasing the PALF loading also increased the amount of water absorption as the biocomposite became more porous.